Tingkat Kepuasan Pasien JKN terhadap Pelayanan Kesehatan di Wilayah Kerja Puskesmas: Studi Literatur Review - Nani Yuniar; Resti Ayu; Ririn Natasya; Sabrina Putri Meylani; Sinta Rizkita; Sunartin Sunartin; Thesalonika Diandra Bara; Wa Ode Muthya Yusrin; Zahratul Jannah; Sitti Adhayanti Putri; Wa Ode Sarfianti; Muh. Zaim Afif Al Fauzi (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2025)
Quality health services are key to improving patient satisfaction among National Health Insurance (JKN) participants. This study aims to systematically review various studies that have been conducted in Indonesia related to the level of JKN patient satisfaction with health services at Community Health Centers. The method used is a literature study by selecting relevant articles published in 2023-2025. Inclusion criteria include articles that discuss the relationship between service quality and JKN patient satisfaction. A total of 11 articles that meet the criteria have been analyzed. The results of the analysis show that the dimensions of service quality that most often influence the level of patient satisfaction are reliability, responsiveness, empathy, and tangibles. Most studies also use a quantitative approach with statistical tests such as chi-square and logistic regression to analyze the relationship between variables. However, not all dimensions always significantly affect the assurance dimension in several studies showing inconsistent results. The conclusion of this study is the importance of improving the quality of health services at Community Health Centers to improve JKN patient satisfaction. Health centers must develop patient-focused service strategies by training human resources, improving service systems, and conducting continuous quality evaluations.